Evaluation of discharge coefficients for bottom rack flow under constant and variable specific energy. Issue 2 (15th March 2023) - Ojha, C. S. P.; Shankar, Vijay; Kumar, Navsal; Chauhan, N. S.
ABSTRACT: Bottom racks are widely used in mountainous regions as intake structures for diverting water from the mainstream for different purposes. Most of the studies on bottom rack flow consider the concept of invariant specific energy. The present study experimentally investigates the specific energy loss in horizontal transverse bottom rack flow for Froude number varying from 0.1 to 1.5, discharge from 0.010 m 3 /s to 0.076 m 3 /s, spacing between bars varying from 0.004 m to 0.028 m and parameter (a/L) varying from 0.041 to 0.102. Experimental investigations suggest that the specific energy loss cannot be neglected in the bottom rack flow. Variation of specific energy loss with Froude number indicates its dependence on flow and rack geometry parameters. Based on the regression analysis of experimental data, the expressions developed for the discharge coefficient 'C1ʹ for the constant specific energy approach are evaluated. The study also developed expressions for the discharge coefficient 'C2ʹ, for variable specific energy. Significant agreement between observed and computed discharge based on developed 'C2ʹ establishes the efficacy of developed expressions.